Evaluasi Efektivitas Pelatihan dan Perilaku Inovatif terhadap Kinerja Karyawan di Hotel Berbintang 4 di Jakarta Timur - Djaswandini, Salma Nadhifa; Goeltom, Vasco Adato H.; Brian, Reagan (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
The hospitality industry continues to grow along with technological advances, changes in consumer interests, and increasing public awareness of the importance of quality service experiences. This study aims to evaluate the effectiveness of training and innovative behavior in four-star hotels in East Jakarta. The method applied in this study is a quantitative approach with a survey design. Data were obtained using a questionnaire distributed to 160 employees of four-star hotels in East Jakarta who had worked for at least one year. The data analysis technique used Partial Least Squares Structural Equation Modeling (PLS-SEM) with the help of SmartPLS 4 software. Training effectiveness is defined as employees’ perceptions of the relevance of the training material, interactive methods, and the application of training in their daily work. Innovative behavior refers to employees' ability to generate, implement, and adapt to new ideas in the workplace. The analysis results show that Training Effectiveness (β = 0.404; p = 0.000) and Innovative Behavior (β = 0.435; p = 0.000) have a significant positive influence on Employee Performance, with an Adjusted R² of 0.612, indicating strong predictive power of the model. The practical implication of this study encourages hotel management to design relevant training programs and foster a work environment that supports innovation. The limitation of this research lies in its geographical scope and the specific type of hotel. Future research is recommended to explore mediating variables such as organizational culture or employee engagement to gain a deeper understanding of the relationships between variables.